1990
DOI: 10.1002/jsfa.2740530209
|View full text |Cite
|
Sign up to set email alerts
|

Thermal inactivation of lectins and trypsin inhibitor activity during steam processing of dry beans (Phaseolus vulgaris) and effects on protein quality

Abstract: A B S T R A C TThe effect of steam treatment on the protein quality and antinutritional factors in beans (Phaseolus vulgaris L ) have been evaluated. The thermal inactivation of total and jhnctional lectins and trypsin inhibitor activity as well as total and available lysine during steam treatment at 102, 119 and 136°C can be described by Jirst order reaction kinetics. Inactivation of trypsin inhibitor factors occurred in two stages with diflerent reaction rates, the initial stage having a higher rate of inact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…5 soaking in acid or basic solutions, and this would lead to different changes in amino acid content. Minka et al 35 also found that amino acid composition was affected by the use of a basic pH solution or distilled water for cooking.…”
Section: Chemical Analyses Of Proteinmentioning
confidence: 99%
“…5 soaking in acid or basic solutions, and this would lead to different changes in amino acid content. Minka et al 35 also found that amino acid composition was affected by the use of a basic pH solution or distilled water for cooking.…”
Section: Chemical Analyses Of Proteinmentioning
confidence: 99%
“…Our recent primary research showed that different protein sources had different percentages and ratios of a-helixes and b-sheets in their protein secondary structures (Yu et al 2004c). These protein structures were highly associated with protein nutritive value.In ruminants, heat-processing has been used to improve the utilisation and availability of nutrients (Yu et al 2002) and inactivate anti-nutritional factors (van der Poel et al 1990), for example by reducing the solubility of the protein, fermentation and metabolism in the rumen, increasing the amount of protein entering the small intestine for absorption and digestion (Yu et al 2002), reducing the hydrogenation of conjugated linoleic …”
mentioning
confidence: 99%
“…In ruminants, heat-processing has been used to improve the utilisation and availability of nutrients (Yu et al 2002) and inactivate anti-nutritional factors (van der Poel et al 1990), for example by reducing the solubility of the protein, fermentation and metabolism in the rumen, increasing the amount of protein entering the small intestine for absorption and digestion (Yu et al 2002), reducing the hydrogenation of conjugated linoleic…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Os métodos de processamento modificam a composição e a disponibilidade de nutrientes em relação ao material cru [10,30]. Porém, alterações químicas produzidas pelo processo de aquecimento podem também diminuir a assimilação de nutrientes, incluindo a absorção de certos nutrientes [2].…”
Section: Amostraunclassified